Parents as Cotherapists with Autistic Children. Parent-Child Program Series, Report No. 3 - Rosenfeld, Anne H.; North Carolina Univ., Chapel Hill. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1978)
Part of a series on early childhood demonstration programs designed to improve early parent-child relationships, stimulate positive child development, and prevent later behavior difficulties, the pamphlet describes the Child Research Project at the University of North Carolina, in which parents were trained to act as cotherapists with their autistic children. On the basis of a diagnostic evaluation, professional staff devised an individualized treatment program plan consisting of outpatient psychotherapy at the treatment center and the training of parents to continue the therapy with the child at home. The rationale for this parent participation is presented, and the diagnosis and assessment aspects of the program are discussed. Also reviewed are both the clinical and home treatment components, parent group meetings, program staffing, and special facilities and resources. Program graduates were found to retain many benefits, though the rate and type of progress of individual children depended, in part, on the severity of their initial biological handicaps. Many showed sufficient lessening of their psychotic symptoms to attend school, though they retained some minor behavioral problems; and some showed dramatic gains in intellectual functioning. (DLS)
Availability: Superintendent of Documents, U.S. Government Printing Office, Washington, D.C. 20402 (Stock No. 017-024-00840-1).
Sponsoring Agency: National Inst. of Mental Health (DHEW), Rockville, MD. Center for Studies of Child and Family Mental Health.
Contract Number: TOPLD-13691-76.
Contract Number: MH-15539.
ERIC Note: For related information, see EC 120 039-043.
Educational level discussed: Preschool Education.
Keywords: Autism; Child Development; Clinical Diagnosis; Home Programs; Parent Child Relationship; Parent Education; Parent Participation; Preschool Education; Program Descriptions; Psychotherapy; Child Research Project; Reports, Descriptive; Collected Works, Serials